Foundations of speech and hearing : anatomy and physiology - Hoit, Jeannette D. (Jeannette Dee), 1954- (Plural Publishing, Inc., 2018)
This comprehensive textbook for undergraduate-level anatomy and physiology courses in communication sciences and disorders programs is neither oversimplified nor excessively detailed. The book is written with clinical endpoints in mind, and only those topics that are ultimately important to understanding, evaluating, and managing clients with speech, hearing, and swallowing disorders are covered.